Experimental investigation of the wetting characteristics of an aqueous ionic liquid solution on an aluminum fin-tube substrate. (April 2018) - Varela, Richard Jayson; Giannetti, Niccolò; Yamaguchi, Seiichi; Saito, Kiyoshi; Wang, Xin-Ming; Nakayama, Hiroshi
Highlights: Wetting characteristics of an ionic liquid solution were experimentally investigated. A method for estimating the wetted area on a solid substrate was introduced. Wetting hysteresis phenomenon and the factors contributing to it were clarified. Three types of wetting patterns on the substrate were observed and explained. The ionic liquid solution is mostly wetting on the aluminum fin-tube substrate. Abstract: In falling film liquid desiccant systems, finding a suitable pair of liquid desiccant and contact surface is of primary engineering interest. This requires knowledge on the wetting characteristics of the liquid on the solid substrate, which consequently requires intensive experimental investigation. In this study, the wetting characteristics of a new ionic liquid aqueous solution in an aluminum fin-tube substrate were experimentally investigated. Then, a simple method for estimating the wetted area on the substrate through image processing was developed. Visual analysis of the surface wetting was also conducted, and three types of wetting patterns are discussed. Experimental results on the static contact angle and contact angle hysteresis suggest that the ionic liquid solution is mostly wetting, and the aluminum surface is slightly to moderately rough. It was found that the wettability of the ionic liquid solution increases as the ionic liquid mass fraction increases. The wetting hysteresis phenomenon and the factors contributing to its occurrence were also clarified. The results from this study would be useful for the development of a new model or improvement of existing wetting models, which can help improve the prediction and control of the heat and mass transfer performance in internally cooled/heated fin-tube contactors.